Personalized Graphene Oxide-Protein Corona in the Human Plasma of Pancreatic Cancer Patients - Di Santo, Riccardo; Digiacomo, Luca; Quagliarini, Erica; Capriotti, Anna Laura; Laganà, Aldo; Zenezini Chiozzi, Riccardo; Caputo, Damiano; Cascone, Chiara; Coppola, Roberto; Pozzi, Daniela; Caracciolo, Giulio (Frontiers in Bioengineering and Biotechnology, 2020)
The protein corona (PC) that forms around nanomaterials upon exposure to human biofluids (e.g. serum, plasma, cerebral spinal fluid etc.) is personalized, i.e. it depends on alterations of the human proteome as those occurring in several cancer types. This may relevant for early cancer detection when changes in concentration of typical biomarkers are often too low to be detected by blood tests. Among nanomaterials under development for in vitro diagnostic (IVD) testing, Graphene Oxide (GO) is regarded as one of the most promising ones due to its intrinsic properties and peculiar behavior in biological environments. While recent studies have explored the binding of single proteins to GO nanoflakes, unexplored variables (e.g. GO lateral size and protein concentration) leading to formation of GO-PC in human plasma (HP) have only marginally addressed so far. In this work, we studied the PC that forms around GO nanoflakes of different lateral sizes (100, 300 and 750 nm) upon exposure to HP at several dilution factors which extend over three orders of magnitude from 1 (i.e. undiluted HP) to 103. HP was collected from 20 subjects, half of them being healthy donors and half of them diagnosed with pancreatic ductal adenocarcinoma (PDAC) a lethal malignancy with poor prognosis and very low five-year survival rate after diagnosis. By dynamic light scattering (DLS), electrophoretic light scattering (ELS), sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and nano liquid chromatography tandem mass spectrometry (nano-LC MS/MS) experiments we show that the lateral size of GO has a minor impact, if any, on PC composition. On the other side, protein concentration strongly affects PC of GO nanoflakes. In particular, we were able to set dilution factor of HP in a way that maximizes the personalization of PC, i.e. the alteration in the protein profile of GO nanoflakes between cancer vs. non cancer patients. We believe that this study shall contribute to a deeper understanding of the interactions among GO and HP, thus paving the way for the development of IVD tools to be used at every step of the patient pathway, from prognosis, screening, diagnosis to monitoring the progression of disease.